Natural soil mediated photo Fenton-like processes in treatment of pharmaceuticals: Batch and continuous approach. (December 2017) - Changotra, Rahil; Rajput, Himadri; Dhir, Amit
Abstract: This paper manifests the potential viability of soil as a cost-free catalyst in photo-Fenton-like processes for treating pharmaceuticals at large scale. Naturally available soil without any cost intensive modification was utilized as a catalyst to degrade pharmaceuticals, specifically ornidazole (ORZ) and ofloxacin (OFX). Soil was characterized and found enriched with various iron oxides like hematite, magnetite, goethite, pyrite and wustite, which contributes toward enhanced dissolution of Fe 3+ than Fe 2+ in the aqueous solution resulting in augmented rate of photo-Fenton reaction. The leached iron concentration in solution was detected during the course of experiments. The degradation of ORZ and OFX was assessed in solar induced batch experiments using H2 O2 as oxidant and 95% ORZ and 92% OFX removal was achieved. Elevated efficiencies were achieved due to Fe 2+ /Fe 3+ cycling, producing more hydroxyl radical leading to the existence of homogeneous and heterogeneous reactions simultaneously. The removal efficiency of solar photo-Fenton like process was also compared to photo-Fenton process with different irradiation sources (UV-A and UV-B) and were statistically analysed. Continuous-scale studies were conducted employing soil either in the form of soil beads or as a thin layer spread on the surface of baffled reactor. Soil beads were found to have satisfactory reusability and stability. 84 and 79% degradation of ORZ and OFX was achieved using soil as thin layer while with soil beads 71 and 68% degradation, respectively. HPLC and TOC study confirmed the efficient removal of both the compounds. Toxicity assessment demonstrates the inexistence of toxic intermediates during the reaction. Graphical abstract: Highlights: Potential viability of naturally available soil as catalyst in photo-Fenton-like processes. Improved degradation efficiency with batch and continuous mode experiments for the removal of ofloxacin and ornidazole. Leaching experiments suggested the simultaneous occurrence of homogeneous and heterogeneous reactions. Soil beads were effectively reused for four times with ≈13% reduction in degradation efficiency for both the pharmaceuticals. Enhanced activity in solar light when compared to UV-A and UV-B.